The Dynamics of Cuba Anticyclones (CubANs) and Interaction With the Loop Current/Florida Current System. Issue 10 (17th October 2017) - Kourafalou, Vassiliki; Androulidakis, Yannis; Le Hénaff, Matthieu; Kang, HeeSook
Abstract: Mesoscale anticyclonic eddies along the northern Cuban coast (CubANs) have been identified in the Straits of Florida, associated with the northward shift of the Florida Current (FC) and the anticyclonic curvature of the Loop Current (LC) at the western entrance of the Straits. The dynamics of CubAN eddies and their interaction with the LC/FC system are described for the first time using satellite, drifter and buoy data, and a high‐resolution model. It is shown that the evolution of CubANs to the south of the FC front complements the evolution of cyclonic eddies to the north of the FC, advancing previous studies on synergy between FC meandering and eddy activity. Two types of CubAN eddies are characterized: (a) a main anticyclonic cell (type "A") within the core of the LC during retracted phase conditions, associated with the process of LC Eddy (LCE) shedding from an extended LC, and (b) an individual, distinct anticyclonic eddy that is released from the main LC core and is advected eastward, along the northern Cuban coast (type "B"). There are also mixed cases, when the process of LCE shedding has started, so a type "A" CubAN is being formed, in the presence of one or more eastward progressing type "B" eddies. CubAN evolution is associated with an increased mixed layer and weaker stratification of the upper ocean along the eddy's track. The cyclonic activity along the Cuban coast and wind‐induced upwelling events also contribute to the evolution and fate of the CubAN eddies. Key Points: Anticyclonic mesoscale eddies along Cuba (CubAN eddies) are identified and characterized for the first time The formation and evolution of CubAN eddies is strongly associated with the variability of the Loop Current/Florida Current system Wind‐induced upwelling and cyclonic eddies along the northern Cuban coast influence the eastward propagation of CubAN eddies